2018
DOI: 10.1186/s12906-018-2278-6
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol prevents nanoparticles-induced inflammation and oxidative stress via downregulation of PKC-α and NADPH oxidase in lung epithelial A549 cells

Abstract: BackgroundExposure to carbon black nanoparticles (CBNPs), a well-known industrial production, promotes pulmonary toxicity through inflammation and oxidative stress. Recent studies show that some polyphenols exert their antioxidant properties through regulation of protein kinase C-α (PKC-α) and NADPH oxidase (Nox) signaling. Resveratrol, a dietary polyphenol in fruits, possesses various health beneficial effects including anti-inflammatory and antioxidative properties. In this study, we aimed to elucidate the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 51 publications
5
20
0
Order By: Relevance
“…Chemical inhibition of AhR and NF-jB by Res significantly attenuated the Pb-induced oxidative stress by reducing the formation of ROS and restored the expression of GSTA1, iNOS, and CYP1A1 in A549 cells exposed to Pb. In agreement with our results, it has been reported that Res prevents nanoparticles-induced inflammation and oxidative stress in A549 cells via inhibition of ROS production and oxidative stress (Hsu et al 2018). In addition, since activation of AhR/ CYP1A1 pathway by Pb is always associated with increased oxidative stress, we postulate here that blocking of AhR would explain the inhibitory effect of Res on ROS production.…”
Section: Control (B)supporting
confidence: 93%
“…Chemical inhibition of AhR and NF-jB by Res significantly attenuated the Pb-induced oxidative stress by reducing the formation of ROS and restored the expression of GSTA1, iNOS, and CYP1A1 in A549 cells exposed to Pb. In agreement with our results, it has been reported that Res prevents nanoparticles-induced inflammation and oxidative stress in A549 cells via inhibition of ROS production and oxidative stress (Hsu et al 2018). In addition, since activation of AhR/ CYP1A1 pathway by Pb is always associated with increased oxidative stress, we postulate here that blocking of AhR would explain the inhibitory effect of Res on ROS production.…”
Section: Control (B)supporting
confidence: 93%
“…Oxidative Medicine and Cellular Longevity resveratrol could also alleviate oxidative and inflammatory factors via inhibiting PKC-α/NOX2 signaling pathway [33]. In our present study, we also confirmed the relationship between PKC-α and NOX2 in U937 monocytes.…”
supporting
confidence: 86%
“…PKC activation also has been identified to play an important part in inflammation and oxidative stress [31,32]. It has been reported that the cross talk between PKC and NOX could induce NOX-dependent ROS production [33]. In rat brain astrocytes, bradykinin could induce inflammation via activating PKC-α-mediated NOX2/ROS signaling pathway [34].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-apoptotic and antioxidant stress-protective effects of RES have been widely investigated. In 2018, Hsu et al (36) revealed that RES could protect A549 human lung epithelial cells against carbon black nanoparticle (CBNP)-induced inflammation and oxidative stress, as cBNPs are known to promote pulmonary toxicity through inflammation and oxidative stress. A previous study used cigarette smoke extract (cSE), which induced apoptosis in a human bronchial epithelial cell model and studied the effects of treatment with or without RES (37).…”
Section: Discussionmentioning
confidence: 99%